Longitudinal study of personal adjustment and social conditions in the Fort McMurray area Vol II.b: Time-Use diaries ... - Ltd., Earl Berger (University of Alberta Library, 1978)
The time-use diary is a data collection instrument intended to furnish a detailed account of daily individual activities by type, sequence, duration and location. Its purpose is to provide a comprehensive picture of how people spend their time. Experience has shown that the time-use diary is a valid instrument for data collection and analysis. Related research in Europe (Szalai, 1965), Britain (BBC,l965) and the U.S. (Robinson and Converse, 1966; Chapin and Hightower, 1966) has shed considerable light on how people spend their leisure and work time on a daily basis. Moreover, it has been used to supplement and enrich information obtained through interviews and surveys. ...